Czech Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This study addresses the following questions: (i) what is the process driving inflation in the Czech Republic? and (ii) in light of the ongoing structural transformation of the economy, can a reliable model of inflation be formulated for analysis and forecasting? The following statistical data are also included in detail: composition of GDP, agricultural production, average monthly earnings, electricity production and consumption, transfers to households, monetary survey, structure of domestic currency deposits, selected interest rates, lending and deposit rates of commercial banks, and so on.